2016
DOI: 10.4236/aces.2016.64044
|View full text |Cite
|
Sign up to set email alerts
|

Fish Swim Bladder-Derived Porous Carbon for Defluoridation at Potable Water pH

Abstract: The levels of fluoride in various ground water sources in East Africa are above the World Health Organization upper limit of 1.5 mg/L. Research on diverse defluoridation technologies has proven that adsorption stands out as an affordable, efficient, and facile technology. Fish swim bladder-derived porous carbon (FBPC) activated by KOH and surface oxidized by nitric acid was successfully investigated as an adsorbent for defluoridation at portable water pH. The FBPC was characterized by scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The mean free energy of adsorption E (kJ mol -1 ) can be calculated to estimate the type of sorption process using the following equation [40]:…”
Section: Dubinin-radushkevich (D-r) Isotherm Modelmentioning
confidence: 99%
“…The mean free energy of adsorption E (kJ mol -1 ) can be calculated to estimate the type of sorption process using the following equation [40]:…”
Section: Dubinin-radushkevich (D-r) Isotherm Modelmentioning
confidence: 99%
“…The deprotonation of uoride adsorption sites at higher pH (>pH 6) leads to a decrease in the quantity of uoride ions removed, owing to the strong competition for binding sites on the adsorbent between OH À and uoride ions. [47][48][49][50]…”
Section: Ph Effect On Adsorption Of Uoride Ionsmentioning
confidence: 99%
“…They found average uptake F capacities to be 1.2 ± 0.3 mg/g and 3.0 ± 1.0 mg/g, respectively. A study to explore activated carbon from fish bladder showed a maximum F removal of 1.43 mg/g [122]. In related work, Kawasaki et al [123] who investigated four types of animal biomass and Singanan [124] who studied certain bone char adsorbents for F removal, reported more or less similar defluoridation potential.…”
Section: Borne Char and Activated Animal Charcoalmentioning
confidence: 99%